Hepatitis C virus eradication decreases the risks of liver cirrhosis and cirrhosis‐related complications (Taiwanese chronic hepatitis C cohort). Issue 10 (21st May 2021) - Hsu, Wei‐Fan; Tsai, Pei‐Chein; Chen, Chi‐Yi; Tseng, Kuo‐Chih; Lai, Hsueh‐Chou; Kuo, Hsing‐Tao; Hung, Chao‐Hung; Tung, Shui‐Yi; Wang, Jing‐Houng; Chen, Jyh‐Jou; Lee, Pei‐Lun; Chien, Ron‐Nan; et al.
Abstract: Background and Aim: It is currently unknown how hepatitis C virus (HCV) eradication with pegylated interferon and ribavirin (PR) therapy affects the incidence of new‐onset liver cirrhosis (LC) in patients without cirrhosis and the incidence of decompensated liver disease (DLD) or hepatocellular carcinoma (HCC) in patients with cirrhosis. Methods: Taiwanese chronic hepatitis C cohort (T‐COACH) is a nationwide HCV registry cohort from 23 hospitals in Taiwan recruited between 2003 and 2015. This study enrolled 10 693 patients with chronic hepatitis C (CHC), linked to the Taiwan National Health Insurance Research Database, receiving PR therapy for at least 4 weeks for new‐onset LC and liver‐related complications (DLD or HCC). Results: Of the 10 693 patients, 1372 (12.8%) patients had LC, and the mean age was 54.0 ± 11.4 years. The mean follow‐up duration was 4.38 ± 2.79 years, with overall 46 798 person‐years. The 10‐year cumulative incidence rates of new‐onset LC were 5.0% (95% confidence interval [CI]: 3.2–7.7) in patients without cirrhosis with a sustained virologic response (SVR) and 21.9% (95% CI: 13.4–32.4) in those without SVR (hazard ratio [HR]: 0.22, P < 0.001). The 10‐year cumulative incidence rates of liver‐related complications were 21.4% (95% CI: 11.1–37.2) in patients with cirrhosis with SVR and 47.0% (95% CI: 11.1–86.0) in those without SVR after adjustment for age, sex, and competing mortality (HR: 0.52, P < 0.001). Conclusions: Hepatitis C virus eradication with PR therapy decreased the incidence of new‐onset LC in noncirrhotic patients and the incidence of liver‐related complications in cirrhotic patients with CHC.